Accelerated aging affects shelf-stability, yield, sensory characteristics, cathepsin activity, and structure of collagen and troponin-T in lower quality beef cuts - Jeneske, Haley Jordan (Kansas State University, 2023)
Cooler aging beef cuts have been the standard method to increase tenderness and value of beef cuts. However, this technique is not time efficient as it may take days to weeks for the cuts to reach the desired level of tenderness. Accelerated aging (AA) is a new method that may significantly improve beef tenderness within just a few hours utilizing a vacuum packager and a warm water bath. However, there are little to no studies on impact of AA on meat quality parameters. Therefore, the aim of this study was to utilize AA at different temperature and time points to determine the impact of AA on shelf stability, yield, sensory characteristics, tenderness, and cathepsin proteolytic activity of two lower quality beef cuts. Triceps brachii (TB) and semimembranosus (SM) were collected and fabricated from 10 USDA Choice carcasses and assigned to one of six treatments: 3 d cooler aged (control), 21 d cooler aged, AA 49ºC for 2 hours, AA 49ºC for 3 hours, AA 54ºC for 2 hours, and AA 54ºC for 3 hours (n=120). Aerobic plate counts (APCs) were conducted on swabs from the steak surfaces and purge collected from the vacuum packaged bags before and after AA. Yield was determined before and after AA as well as before and after grilling. Instrumental color, Warner-Bratzler Shear Force (WBSF), trained sensory panels, proximate analysis, lipid oxidation, cathepsin zymography, troponin-T degradation, soluble/insoluble collagen content, total collagen in the purge, and perimysial peak transitional temperature and enthalpy were measured. The results showed that AA can decrease APC counts on meat surface and in purge (P < 0.01), decrease redness (P < 0.01), increase lightness (P < 0.05), and decrease yield (P < 0.01) of the steaks. Lower shear force measurements were also found in AA steaks compared to those from the control (P < 0.01), with the AA 54ºC treatment being comparable to 21 d cooler aging. However, the trained sensory panel determined AA steaks were less juicy (P < 0.01) and less flavorful (P < 0.05) than the control and 21 d cooler aged samples, and AA steaks were less tender (P < 0.01) even though there was lower connective tissue recorded (P < 0.01). There was no off-flavor in AA steaks (P > 0.05), although lipid oxidation was slightly higher in AA samples than in the control steaks (P < 0.01). The AA treatment stimulated cathepsin activity where AA 49ºC for 3 hours displayed the highest activity (P < 0.05), which led to the additional degradation of troponin-T (P < 0.01) and solubilization of stromal proteins (P < 0.01). Although AA is an economical and time-efficient method to increase tenderness of lower-quality beef cuts, further research is needed to determine strategies to mitigate the loss of moisture and decrease in juiciness from AA treatments.
Keywords: Trained panel; Differential scanning calorimeter; Collagen; Enzymatic activity; Connective tissue; Meat tenderness